ANALISIS PENGARUH KOMPETENSI SYARIAH, KOMPENSASI ISLAMI DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN (Studi Kasus Bank Muamalat Cabang Ternate) - Maryani, Ay; Rusmahafi, Hayatul Muthmainnah (Ekonomi Islam, 2017)
The purpose of this research is to analyze the impact of sharia competencies, Islamic compensation and Islamic Spiritual Intelligence of personal work performance at Bank Muamalat Branch Ternate. The data obtained in the research is primary data taken from questionnare were distributed to employees at Bank Muamalat Branch Ternate. Data analysis technique in this research using multiple linear regression analysis using SPSS version 16.0.The result of this research shows from all of three variables, Islamic spiritual intelligence is the only one that have significant effect on personal work performance of Bank Muamalat Branch Ternate